A study of attention and imagery capacities in badminton players - Gulsum Bastug; Ali Agılonu; Nuri Balkan (Türk Spor ve Egzersiz Dergisi)
The purpose of the research was to analyze imagery and attention capacities in badminton players. 85 players aged 16-18 who participated in Badminton Turkey Championship in 2016, were involved in this research. Bourdon Attention Test for the attention levels of players participating in the research, Sport Imagery Questionnaire (SIQ) developed by Hall et al. for their imagery capacity were used herein. In evaluation of data, frequency analysis, t-test and correlation analysis were done. In conclusion; any significant differences were not found between imagery capacity and gender variable in badminton players. But a significant difference was found between sport age, cognitive imagery and motivational general competence. When cognitive imagery values increase, motivational general arousal values increase. And when motivational general competence values go up, motivational specific imagery rate rises. In badminton players there was a significant relation between imagery and attention. There was a positive relation between motivational specific imagery and attention. When capacity for motivational specific imagery rises, attention capacity rises in players. When players win the match or perform well, they imagine to be appreciated (Motivational Specific Imagery), this positively affects attention capacity. Imagery trials accompanied by physical trainings are influential for improving players’ attention capacity.